84 Reducing waste and improving patient safety: introduction of the on-call doctor's bag. (12th November 2018) - Stahl, Matthew; Prasad, Alok; Vasita, Ekta; Patel, Neil; Levi, Sassoon
Abstract : We introduced an on-call doctors bag for the Foundation Year One (FY1) doctor's on-call medical ward cover at Wexham Park Hospital. These on-call shifts are extremely busy with the FY1 covering 14 different wards. Time is wasted locating essential equipment on unfamiliar wards. Literature over the last 5 years has calculated that junior doctors spend on average 29 hours accessing treatment room and approximately 4 working days collecting equipment over a year. 1 These delays can compromise patient safety in emergencies as well as contributing to daily inefficiency and lower job satisfaction. A pre-intervention questionnaire using a 5-point Likert Scale identified 90% of FY1 respondents (n=22) at felt that significant time was wasted looking for equipment on unfamiliar wards. A paramedic sling-bag (£90) was purchased as an on-call doctors bag. The bag was stocked with the relevant equipment and was made available to all FY1s for their medical on-call. The bag was restocked by the ward manager at the end of each shift. A post-intervention questionnaire was distributed to FY1 doctors. 100% of respondents (n=20) agreed the on-call bag helped them to be more efficient. 100% of respondents agreed less time was spent collecting equipment on the wards with the bag. 95% of respondents stated that they will continue to use the on-call bag. 10 simulated trials were performed comparing the time taken to collect equipment on 8 different wards. 6 volunteer final year medical students unfamiliar with the hospital environment were asked to collect equipment for four common on-call tasks (ABGs, cannulas, phlebotomy and blood cultures) on 8 different wards with and without the on-call bag. In every trial performed, the student with the on-call bag obtained the equipment faster than the student without the bag. The median time saved across all procedures and wards was 3 min 26 s (range 57 s – 7 min 29 s). The on-call doctor's bag is invaluable in reducing waste and increasing the number of on-call jobs that can be completed per shift. It reduces the time wasted in collecting essential equipment when treating the unwell or deteriorating patient. Reference: Karapinar Y, Habib A, Sawyerr H. Improving time efficiency gathering equipment in the treatment room. BMJ Open Quality 2017;6.